Wulwodynia – a multidisciplinary approach, which also applies to postmenopausal women - Baszak-Radomańska, Ewa; Radomański, Tomasz (Menopause Review/Przegląd Menopauzalny, 2011)
Wulwodynia is defined as a discomfort or pain in the entrance to the vagina, urethra, perineum or anus without perceptible pathological changes. Postmenopausal women often experience vaginal dryness (45%), and burning (10%), whereas pain during sexual intercourse feels 1/3 of women after menopause (provoked wulwodynia). Differences in the management of patient with post-menopausal wulwodynia is getting a biopsy of the vulva in justified cases, which is obviously not necessary in the vulvar pain patients of childbearing age. Another difference is that the most effective treatment consisting of local estrogenotherapy. The article presents the spectrum of therapeutic intervention.